IDENTIFICATION OF RAT MEATBALLS IN TRADITIONAL MARKET IN AREA OF JAKARTA USING REAL TIME–PCR - Septiani, Triayu (Pusat Kajian Halal Undip, 2020)
Meat is one of protein source who was often consumed. Consume halal food are obligation for every moslem. Beef and chicken meat is the most popular food consumed in Indonesia, processed beef and chicken meat is the most consumed, example meatballs. Usually processed meat food from beef are often counterfeiting with rat meat. Rat is generally become pests in Indonesia, such in rice fields and rice storage warehouses, Rat has orange-brown fur and has sized between 304-400 mm. Rattus rattus or black rats are mice that can be found all over the world. The analysis technique in biology molecular, such RT – PCR becomes a promises technique for detection or identification contaminant DNA in meat processed food. All of the samples has been result of extraction then analyzed the purity and has purity range between 1.8 to 1.89. Results of Real Time PCR to detection rat DNA contaminants in meatball samples showed that all of the samples (forty-six samples) who was analyzed, five samples showed negative detected samples and forty-one other samples has Cp value range between 27.02 to 37.08, were indicated to be positively indicated from amplified samples, but the Cp value indicated in the samples was indicated positive tend to be much higher than the positive control Cp value, which is 16,26.